Assessing the dry matter intake and enteric methane emissions of pre-partum dairy cows offered grass clover or grass-only silage from two different silage systems - Kennedy, Michael; Lahart, Ben; Herron, Jonathan; Boland, Tommy M.; Fleming, Christina; Egan, Michael (Frontiers in Animal Science, 2024)
Over the winter period, the low grass growth and availability in pasture-based dairy systems results in animals being housed and predominantly fed a diet of grass silage. There is limited availability of methane (CH4) data evaluating the impact of forage type on dairy cows over the pre-partum period. The objective of the current experiment was to evaluate the impact of feeding grass clover (GC) silage and grass-only (GO) silage on the dry matter intake (DMI) and enteric CH4 emissions of dairy cows pre-partum. A complete randomised block design was utilised for the 6-week experiment over two winter periods: from December 2020 to January 2021 and from December 2021 to January 2022. In each year, 30 non-lactating pregnant dairy cows were randomly allocated to two treatments (n = 15). In both years, cows in the GC treatment were offered grass clover bale silage, while cows in the GO treatment were offered grass-only pit silage. The DMI and gaseous emissions of individual animals were monitored daily using Hokofarm RIC (roughage intake control) feed stations and the GreenFeed technology. GC silage consistently had greater (p< 0.05) organic matter (OM) digestibility and lower (p< 0.05) neutral detergent fibre (NDF) and acid detergent fibre (ADF) contents when compared with GO silage. Cows in the GC treatment had significantly greater (p< 0.05) total DMI (TDMI) compared with cows in the GO treatment. The daily CH4 emissions (in grams per day) were not affected by treatment; however, cows in the GC treatment had reduced (p< 0.05) CH4 yield (in grams per kilogram TDMI). Offering dairy cows GC silage over the pre-partum period resulted in greater DMI with reduced CH4 yield when compared with cows offered GO silage.